FcgRIII Deficiency and FcgRIIb Defeciency Promote Renal Injury in Diabetic Mice. (22nd August 2019) - Zhang, Rui; Wang, Tingli; Yin, Qinhua; Zhang, Junlin; Li, Li; Guo, Ruikun; Han, Qianqian; Li, Hanyu; Wang, Yiting; Wang, Jiali; Gurung, Pramesh; Lu, Yanrong; et al.
Abstract : The immune system is involved in the development of diabetes complications and IgG Fc gamma receptors (FcgRs) are key immune receptors responsible for the effective control of both humoral and innate immunity. We investigated the effects of members of the FcgR superfamily into both the streptozotocin plus high fat-induced type 2 diabetes and high fat diet (HFD) models. FcgRIII -/- diabetic mice and FcgRIIb -/- diabetic mice had elevated levels of serum creatinine compared with wildtype (WT) diabetic mice. Renal histology of diabetic FcgRIII knockout and FcgRIIb knockout mice showed mesangial expansion and GBM thickening; the mechanistic study indicated a higher expression of TGF- β 1, TNF- α, and p-NF κ B-p65 compared with wild type mouse. The HFD mouse with FcgRIII knockout or FcgRIIb knockout had increased biochemical and renal injury factors, but oxLDL deposition was higher than in FcgRIII -/- diabetic mice and FcgRIIb -/- diabetic mice. In vitro we further examined the mechanism by which the Fc gamma receptor promoted renal injury and transfected glomerular mesangial cells (GMCs) with FcgRI siRNA attenuated the level of TGF- β 1, TNF- α expression. In summary, FcgRI knockdown downregulated kidney inflammation and fibrosis and FcgRIIb knockout accelerated inflammation, fibrosis, and the anomalous deposition of oxLDL whereas FcgRIII deficiency failed to protect kidney from diabetic renal injury. These observations suggested that FcgRs might represent a novel target for the therapeutic intervention of diabetic nephropathy.